HEMOXCell, a New Oxygen Carrier Usable as an Additive for Mesenchymal Stem Cell Culture in Platelet Lysate‐Supplemented Media. Issue 4 (22nd March 2017) - Le Pape, Fiona; Cosnuau‐Kemmat, Lucie; Richard, Gaëlle; Dubrana, Frédéric; Férec, Claude; Zal, Franck; Leize, Elisabeth; Delépine, Pascal
Abstract: Human mesenchymal stem cells (MSCs) are promising candidates for therapeutic applications such as tissue engineering. However, one of the main challenges is to improve oxygen supply to hypoxic areas to reduce oxygen gradient formation while preserving MSC differentiation potential and viability. For this purpose, a marine hemoglobin, HEMOXCell, was evaluated as an oxygen carrier for culturing human bone marrow MSCs in vitro for future three‐dimensional culture applications. Impact of HEMOXCell on cell growth and viability was assessed in human platelet lysate (hPL)‐supplemented media. Maintenance of MSC features, such as multipotency and expression of MSC specific markers, was further investigated by biochemical assays and flow cytometry analysis. Our experimental results highlight its oxygenator potential and indicate that an optimal concentration of 0.025 g/L HEMOXCell induces a 25%‐increase of the cell growth rate, preserves MSC phenotype, and maintains MSC differentiation properties; a two‐fold higher concentration induces cell detachment without altering cell viability. Our data suggest the potential interest of HEMOXCell as a natural oxygen carrier for tissue engineering applications to oxygenate hypoxic areas and to maintain cell viability, functions and "stemness." These features will be further tested within three‐dimensional scaffolds.